Performance of PSMA-targeted radiotheranostics in an experimental model of renal cell carcinoma - Singh, Rajan; Thotakura, Anand K.; Alati, Suresh; Lisok, Alla; Jiang, Zirui; Merino, Vanessa F.; Minn, Il; Yadav, Santosh; Markowski, Mark C.; Ged, Yasser; Pavlovich, Christian P.; Singla, Nirmish; et al. (Frontiers in Oncology, 2024)
Renal cell carcinoma (RCC) represents cancer originating from the renal epithelium and accounts for > 90% of cancers in the kidney. Prostate-specific membrane antigen (PSMA) is overexpressed in tumor-associated neovascular endothelial cells of many solid tumors, including metastatic RCC. Although studied in several small clinical studies, PSMA-based imaging and therapy have not been pursued rigorously in preclinical RCC. This study aimed to evaluate the preclinical performance of PSMA-based radiotheranostic agents in a relevant murine model. A PSMA overexpressing murine cell line, PSMA+ RENCA, was developed by lentiviral transduction. PSMA-based theranostic agents, 68Ga-L1/ 177Lu-L1/ 225Ac-L1, were synthesized in high radiochemical yield and purity. 68Ga-L1 was evaluated in small animal PET/CT imaging in flank and PET/MR imaging in orthotopic models. Cell viability studies were conducted for 177Lu-L1 and 225Ac-L1. Treatment studies were performed using 225Ac-L1 in PSMA+ RENCA in the flank model. Cellular uptake of 68Ga-L1, 177 Lu-L1, and 225Ac-L1 confirmed the specificity of the agents to PSMA+ RENCA cells rather than to RENCA (wt) cells. PET/CT images displayed >7-fold higher accumulation of 68Ga-L1 in PSMA+ RENCA compared to RENCA (wt) in flank implantation at 1 h. A two-fold higher accumulation of 68Ga-L1 was observed in orthotopic tumors than the normal kidneys during 1-3 h post-injection. High lung uptake was observed with 68Ga-L1 PET/MR imaging 3 weeks after orthotopic implantation of PSMA+ RENCA due to spontaneous lung metastases. The imaging data were further confirmed by immunohistochemical characterization. 225Ac-L1 (0-37 kBq) displayed a dose-dependent reduction of cell proliferation in the PSMA+ RENCA cells after 48 h incubation; however, no effect was observed with 177Lu-L1 up to 144 h post-inoculation. Animals treated with 225Ac-L1 at 1 wk post-tumor inoculation displayed significant tumor growth delay and longer median survival of 21 d and 24 d for the treatment groups 37 kBq and 2×37 kBq, respectively, compared to the vehicle group. The results suggest that a theranostic strategy targeting PSMA, employing PET and alpha-particle-emitting radiopharmaceuticals, enabled tumor growth control and enhanced survival in a relevant immunocompetent murine model of RCC. These studies provide the rationale for clinical studies of PSMA-targeted theranostic agents in patients with RCC.